Note—A Note on the Deterministic Capacity Problem - Giglio, Richard J. (Management Science, 1973)
This note extends some work by Manne [Manne, A. S. 1961. Capacity expansion and probabilistic growth. Econometrica 29 (4, October).], which dealt with the case where demand was growing linearly, and also some work by Srinivasan [Srinivasan, T. N. Geometric rate of growth of demand. Investments for Capacity Expansion 150–156.] who assumed demand was growing geometrically. The difference lies in the form of the demand which here is assumed to be growing at a decreasing rate.